PrintMaster Gold 16 [electronic resource - broderbund (Novato, CA : Broderbund, c2004, 2004)
Create greeting cards; invitations; CD labels; calendars; banners; photo projects; party sets; 3D crafts; family newsletters and more
1
Keywords: CD.ROM (Children ); Computer graphics -- Software; Desktop publishing -- Software; Printing -- Software